Center of Pressure Displacement of Standing Posture during Rapid Movements Is Reorganised Due to Experimental Lower Extremity Muscle Pain. - Shinichiro Shiozawa; Rogerio Pessoto Hirata; Thomas Graven-Nielsen (PLoS ONE, 2015)
Background Postural control during rapid movements may be impaired due to musculoskeletal pain. The purpose of this study was to investigate the effect of experimental knee-related muscle pain on the center of pressure (CoP) displacement in a reaction time task condition. Methods Nine healthy males performed two reaction time tasks (dominant side shoulder flexion and bilateral heel lift) before, during, and after experimental pain induced in the dominant side vastus medialis or the tibialis anterior muscles by hypertonic saline injections. The CoP displacement was extracted from the ipsilateral and contralateral side by two force plates and the net CoP displacement was calculated. Results Compared with non-painful sessions, tibialis anterior muscle pain during the peak and peak-to-peak displacement for the CoP during anticipatory postural adjustments (APAs) of the shoulder task reduced the peak-to-peak displacement of the net CoP in the medial-lateral direction (P<0.05). Tibialis anterior and vastus medialis muscle pain during shoulder flexion task reduced the anterior-posterior peak-to-peak displacement in the ipsilateral side (P<0.05). Conclusions The central nervous system in healthy individuals was sufficiently robust in maintaining the APA characteristics during pain, although the displacement of net and ipsilateral CoP in the medial-lateral and anterior-posterior directions during unilateral fast shoulder movement was altered.